Hypertension eHealth Intervention National Upscaling - Simons, Luuk P.A. (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Hypertension is a main risk factor worldwide for premature death. After having conducted several hypertension eHealth interventions locally, we now study national upscaling. Innovation diffusion is generally challenging; there are additional challenges in eHealth and even more so for prevention interventions. Still, the Dutch GLI-system (Combined Lifestyle Intervention) appears promising for enabling national innovation diffusion. The local 'Blood Pressure Challenge' intervention has been redesigned to a 'Blood Pressure GLI'-format. This new service concept is evaluated using Rogers' framework of innovation diffusion in a user study with n=7 potential adoption partners (physiotherapists, dietitians and lifestyle coaches) having GLI execution experience. Main findings are that the Dutch GLI-system appears supportive for innovation diffusion and that the respondents see clear benefits in the Blood Pressure GLI service concept and its tangible blood pressure improvements. Finally, the user feedback suggested several service redesign improvements.